Populus spp., respuestas clonales de crecimiento en suelos Argiudoles y Hapludoles, de la provincia de Buenos Aires, Argentina - Baridón, Juan Esteban (2008)
The aim of this study was to assess the growth of clones of Populus spp. in the soil types Hapludolls and Argiudolls, of the mainland in the Buenos Aires province. The study took place in Alberti (34°50’ S, 60°30’ W, 35 m.a.s.l.), Buenos Aires, Argentina. Five clones of Populus spp. were studied: ‘Stoneville 66’ (‘Delta Gold’); ‘Conti 12’, ‘568-1’, ‘610-31’ and ‘564-17’. The experimental design consisted of randomized complete blocks with sub-samples. There were three blocks on three types of soil: a Typic Hapludoll, Entic Hapludoll, and a Typic Argiudoll. Physical and chemical characterizations of each soil type were performed. The average values of total basal area and height were recorded. The results were subjected to analysis of variance, and means were separated according to Tukey’s test. An analysis of genotype-soil interaction was performed. No significant interaction between clone factor and soil factor was obtained. Clones ‘Stoneville 66’, and ‘568-1’ did not differ significantly among themselves and displayed better growth. Therefore, no specific associations between these clones and the soils existed. These results should be valid and applicable for a large amount of land because of the wide distribution of Argiudoll and Hapludoll soils.